Penanaman Aqidah Islam Ditinjau dari Ontologi dan Epistemologi Islam di Pondok Pesantren: Studi Kasus di Madrasah Aliyah Pondok Pesantren Luqmanul Hakim - Mujiburrohman, Mujiburrohman; Kurniawan, Ilham (TSAQOFAH, 2026)
In the midst of modernity, the understanding of Tauhid in Islamic education is often trapped in dogmatic memorisation without rational and spiritual depth, thus necessitating a more philosophical and reflective approach to the concept of divine oneness. This study aimed to analyse the concept of Tauhid through two main philosophical approaches, namely ontology and epistemology, as well as its implementation in Islamic education at MA Lukmanul Hakim. A qualitative method was employed through field research using observation, interviews, and content analysis to explore how Tauhid is understood as the reality of existence (ontology) and how knowledge of divine oneness is acquired and validated (epistemology). The findings show that, ontologically, Tauhid establishes Allah as wājib al-wujūd (absolute existence) who is entirely distinct from creation (laysa kamithlihi shay’un), whereas epistemologically the understanding of Tauhid is constructed through the integration of revelation (dalil naqli), reason (dalil ‘aqli), and spiritual experience (‘irfānī). The internalisation of Tauhid values in the educational process is carried out by harmonising science and religion, whereby science explains the mechanisms of the natural world (how), while Tauhid explains the intellectual agent behind them (who). The study concludes that a philosophical approach to Tauhid not only deepens students’ theoretical understanding but also provides intellectual immunity for the younger generation in facing the challenges of materialism and secularism in contemporary Islamic education.